ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE SERVQUAL DI SPBU PASTI PAS MEUREUBO KABUPATEN ACEH BARAT - Herdi Susanto; Fuadri Fuadri; Yuliani Yuliani (Universitas Teuku Umar, 2016)
Purpose of this study is to determine the quality of services in accordance with Standard Operating Procedures (SOP) minimum service standards Pertamina Pasti Pas gas stations and to determine the degree of influence the quality of services provided Pasti Pas Meureubo gas stations to customer satisfaction. Method used to analyze the quality of service to satisfaction costumer is Servqual method which is the method used to measure the quality of service of the attributes of each dimension, so the value will be gap (the gap) is difference between consumer perceptions of the services that have been received with expectations to be received. The measurement method is to measure the quality of service of the attributes of each dimension, so that would be obtained value gap is the difference between consumer perceptions of service received by the consumer expectations on the services that will be received. However, in general there has been no uniformity limitations on the concept of quality servive (servqual). Data analysis Pearson correlation coefficients were processed through a computerized statistical software. Based on the findings of the research data, can be obtained by the correlation coefficient (r) of rhitung of 0, 886 were identified at the level of 0.01. Based on the statement that if r> 0, then the hypothesis is accepted and positive direction. Because calculations show that rhitung r (0, 886)> rtabel (0.198), meaning Ha (alternative hypothesis) Ho accepted and rejected. By this it can be seen that customer satisfaction (customers satisfaction) influence on the service